Vegetation productivity in natural vs.cultivated systems along water availability gradients in the dry subtropics - Baldi, Germán (2016)
Fil: Baldi, Germán. Universidad Nacional de San Luis. Grupo de Estudios Ambientales (IMASL). San Luis, Argentina.